How to develop confident mathematicians in the early years : a guide for practitioners and parents - Cotton, Tony (Routledge, 2019)
"Showing how everyday experiences can be used to encourage early mathematical thinking, this book will help you to confidently support young children's mathematical development through play. Developing Confident Mathematicians in the Early Years clearly explains the stages of mathematical development from birth to five years. It considers how practitioners and parents can create a mathematically rich environment and then offers a wealth of practical activities and suggestions for adult-child interactions to enhance children's mathematical learning. Features include: - 60 activities each covering a core area of mathematical experience - measurement, algebra, data handling, counting and calculation. - clear explanations of the mathematics taking place in each activity and how this forms the foundation for mathematical learning in the future. - practical suggestions for home learning and working in partnership with parents - links to the EYFS and National Curriculum Offering a rich source of ideas using everyday resources, this practical text will inspire practitioners and parents to nurture young children's innate confidence and ability in mathematics"--